The effectiveness of an early intervention program based on employing educational activities in developing basic science skills for hearing impaired children (Journal of Hama University, 2023)
The research aimed to reveal the effectiveness of a proposed early intervention program based on employing educational activities in developing basic science skills for hearing-impaired children. The research sample consisted of 12 kindergarten children with hearing disabilities.To achieve the objectives of the research and test the validity of its hypotheses, the following tools were used:A proposed program based on employing educational activities to provide hearing-impaired children with basic science skills.- Illustrated Basic Science Skills Scale for Hearing Impaired Children.The research reached the following results:1- The effectiveness of the proposed program based on employing educational activities in developing basic science skills for children with hearing disabilities.2- There are statistically significant differences between the mean scores of the children of the experimental group in the pre and post measurements on the scale of basic science skills for kindergarten children with hearing disabilities and its sub-dimensions, and the differences are in favor of the post measurement.3- There are no statistically significant differences between the mean scores of the children of the experimental group in the post and follow-up measurements on the scale of basic science skills for kindergarten children with hearing disabilities and its sub-dimensions.
Keywords: early intervention, educational activities, basic science skills, aud; early intervention, educational activities, basic science skills, auditory children